2018
DOI: 10.1097/fbp.0000000000000349
|View full text |Cite
|
Sign up to set email alerts
|

Decreases in smoking during treatment for methamphetamine-use disorders: preliminary evidence

Abstract: Despite high rates of smoking (70-90%) and the severely negative impact of smoking on physical and mental health, only 12% of individuals receiving stimulant-use disorder treatment also receive smoking-cessation treatment. The aim of this investigation was to examine the effect of a contingency management (CM) intervention targeting methamphetamine (MA) use on cigarette smoking. Sixty-one adults with MA-use disorders who were smokers were assigned to CM or standard psychosocial treatment. Rates of smoking-nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Lastly, and in line with some of the observations among patients with co-occurring addictions or MI, there is another line of developing inquiry focused on examining the “off-target” effects of CM on co-occurring addiction behavior in an effort to leverage such observed crossover effects. In published examples of this effect, CM exhibited an apparent off-target effect on smoking among smokers who were undergoing methamphetamine-use-disorder treatment 64 and a population of smokers who were also patients with SMI undergoing treatment for psychostimulant use 56 and alcohol-use disorder. 6 It has also been demonstrated that CM indirectly reinforces treatment attendance when attendance is mandatory in order to provide the required urine sample.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, and in line with some of the observations among patients with co-occurring addictions or MI, there is another line of developing inquiry focused on examining the “off-target” effects of CM on co-occurring addiction behavior in an effort to leverage such observed crossover effects. In published examples of this effect, CM exhibited an apparent off-target effect on smoking among smokers who were undergoing methamphetamine-use-disorder treatment 64 and a population of smokers who were also patients with SMI undergoing treatment for psychostimulant use 56 and alcohol-use disorder. 6 It has also been demonstrated that CM indirectly reinforces treatment attendance when attendance is mandatory in order to provide the required urine sample.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, research has also demonstrated that implementing smoking cessation treatment does not negatively affect substance use outcomes, including treatments delivered for stimulant use disorder (SUD; Budney et al, 1993; Patkar et al, 2006; Radzius et al, 1998). Given the strong relationship between cigarette smoking and stimulant use, it’s plausible that by introducing a combination of smoking cessation treatments, stimulant use may be indirectly treated as well (McDonell et al, 2014; McPherson et al, 2018). To formally test this idea, the most powerful methodological approach should be considered to determine whether the influence of one medication or behavioral therapy can provide relief for not only the target disorder, but also other related disorders.…”
Section: Parallel Growth Modeling (Pgm)mentioning
confidence: 99%
“…We used a one-tailed alpha error rate of 0.05 as the threshold for statistical significance. We replicated GEE models using multiple imputation to handle the missing values in a sensitivity analysis, assuming data were missing at random, and in a manner consistent with previous CM studies and best-practice handling of missing data in clinical trials [21,22,[36][37][38][39][40][41][42]. All analyses were performed using Stata version 14 software.…”
Section: Statistical Analysesmentioning
confidence: 99%